A cross-sectional study to explore the reasons to visit a quack for prosthodontic solutions - Swapnil Parlani; Shuchi Tripathi; Anjali Bhoyar (Wolters Kluwer Medknow Publications, 2018)
Purpose: Since the services of a qualified practitioner are not easily accessible to the vast majority of the population, the gap is filled literally at the roadside by the ubiquitous unqualified practitioner. The present article emphasizes on the outcome of prosthesis which the quacks deliver for the replacement of natural teeth. Materials and Methods: In the present study, we had explored the reason why people visit these quacks, the complications which they face after using fixed dentures delivered by the quack and some solutions to tackle quackery. Data were recorded as a closed-ended questionnaire for 132 participants. Results: Nearly 64% of subjects were facing a problem with the denture and 74.2% of the participants were not even aware of any qualified practitioner. Most common reason to visit the quack was lack of awareness; other reasons were economy, proximity to house, comfortable fixed option, single appointment, and referrals. Conclusion: Awareness and orientation programs are possible solutions to spread knowledge, change attitudes, and practice. In addition to that, there should be strict laws abolishing the practice of unqualified practitioner.